PERKAWINAN ANTARA ETNIS MINANG DENGAN ETNIS ACEH DALAM KONTEKS KOMUNIKASI ANTAR BUDAYA DI KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Zulhamdi Zulhamdi; Reni Juliani (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2022)
This research was conducted to find out the intercultural communication that took place between the ethnic Acehnese and the Minang ethnicity in the ethnic intermarriage that took place in the Johan Pahlawan Subdistrict. The research method used is a qualitative research method with a descriptive approach, data collection techniques using observation and interviews. The results show that intercultural communication that has been carried out by both ethnicities has been going on for a long time, Indonesian and Minang languages are the main factors in supporting intercultural communication that occur, then one obstacle in intercultural communication that occurs is custom in ethnic Acehnese marriages.Keywords: Marriage, Minang Ethnicity, Acehnese Ethnicity, Communication, and Interculturalism